One Day at a Time, Four Decades Apart: An Analysis of the Doxic, Mimetic, and Diagnostic Performances in the Original and Rebooted Pilots of the Classic Norman Lear Show - (:unkn) unknown (My University, 2024)
In the modern era, it has become easier than ever to watch serial shows, whether they air on primetime television or are released on subscription video-on-demand (SVOD) services. However, the lack of Latinx representation in these shows is severely lacking. This is why shows like the rebooted Norman Lear classic One Day at a Time are so important to the audiences it reaches. Shows with Latinx actors and storylines can impact the way their Latinx audience members view themselves and break the stereotypes associated with them (Contreras 2021). By analyzing several scenes from both the 1975 and 2017 pilot episodes as Falk Moorean diagnostic events, I will show how the characters in these shows use continuous and discontinuous personnages to be various other family members in arguments to support the new doxic aspects of their lives in a single-parent household, how these shifts are used by the mother characters, Ann (1975) and Lupe (2017), to counter the hypersexualization of young divorced women that has continued in US society, and the importance of these stories being told by people who belong to the marginalized communities they represent.
Keywords: doxa; mimetic constructs; diagnostic events; television; performance